2003
DOI: 10.1002/cncr.11524
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of the tumor necrosis factor family in benign and malignant hematologic disorders

Abstract: Tumor necrosis factor (TNF), originally identified as a factor produced in the serum of endotoxin-injected animals, is a cytokine that mediates tumor necrosis. To date,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 135 publications
1
64
0
2
Order By: Relevance
“…40 The TNF-␣ -857 T allele has been associated with a decreased risk of Crohn's disease, 22,40 another immune-mediated disease characterized by marked lymphocyte infiltration. Since dysregulated TNF-␣ signal transduction contributes directly to the transformed state in many human lymphoid cancers, especially those of B-cell origin, 41 this may partly explain why the genetically determined low TNF-␣ secretor (TNF-␣ -857 T allele) protects against the development of maltoma. Collectively, these data indicate a central role of TNF-␣ in lymphoid proliferation and a decrease of NF-B transactivation by the TNF-␣ -857 T allele.…”
Section: Discussionmentioning
confidence: 99%
“…40 The TNF-␣ -857 T allele has been associated with a decreased risk of Crohn's disease, 22,40 another immune-mediated disease characterized by marked lymphocyte infiltration. Since dysregulated TNF-␣ signal transduction contributes directly to the transformed state in many human lymphoid cancers, especially those of B-cell origin, 41 this may partly explain why the genetically determined low TNF-␣ secretor (TNF-␣ -857 T allele) protects against the development of maltoma. Collectively, these data indicate a central role of TNF-␣ in lymphoid proliferation and a decrease of NF-B transactivation by the TNF-␣ -857 T allele.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 However, many human tumors including hematologic malignancies are partially or completely resistant to monotherapy with TRAIL, limiting its therapeutic utility. [10][11][12][13] In childhood acute lymphoblastic leukemia (ALL), we previously reported that 50% of pretreatment samples are resistant to TRAIL-induced apoptosis and that TRAIL even stimulates survival and proliferation in some of the resistant patients. 14 This highlights the demand to develop TRAIL-based combination therapies that counter resistance mechanisms of acute leukemia cells toward TRAIL to ensure the success of TRAIL in the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…plastic large cell lymphoma (ALCL), multiple myeloma, and adult T-cell leukemia (2)(3)(4). The fact that CD30 is present normally on only a very small fraction of activated B-and T-cells makes it an attractive target for therapeutic intervention.…”
mentioning
confidence: 99%